MEMPERSIAPKAN PRAKTEK DOKTER GIGI MENJELANG INDONESIA SEHAT 2010 - Gusti Rizali Noor (Faculty of Dentistry, Universitas Indonesia, 2015)
On March1, 1999 the President of the Republic of Indonesia launched the "Movement For Health-oriented Development" as a national development strategy to realize Healthy Indonesia 2010. Healthy Indonesia 2010 visualizes the health status of the people of Indonesia as better than today. The strategy of achieving this condition implies 4 issues, i.e. health paradigm - health-oriented development, professionalism, JPKM (managed health care), and decentralization. The Health Paradigm focuses on promotive-preventive, proactive, community-centered activities, and builds upon the active participation and empowerment of the community. JPKM is hoped to be one way of iplementing these necessary changes and reform. Dentists working in Goverment or in private facilities must anticipate this change in vision (health paradigm) in approach (family dentist) and in service-orientation (promotive-preventive), among others by increasing his/her knowledge about the implementation mechanisms of JPKM, about recent development in promotive-reventive measures, by sharpening his/her capability in diagnosing and treating dental diseases, ny knowing how to calculare capitation as a means of paying dental services, and by enhancing his/her capability in evaluating and examinig the contents of a JPKM contract. This change in vision, attitude and capability as mentioned before has to be achieved by arranging special courses sponsored by the Department of Health, the Faculties of Dentistry and the Indonesian Dental Association.